Formulation Strategy to Prevent Sticking in Calcium Carbonate–Cholecalciferol Chewable Tablets: The Role of Citric Acid - Hestiary Ratih; Oke Setiawan Gosepa; Fikri Alatas; Titta Hartyana Sutarna (JURNAL INFO KESEHATAN, 2026)
The sticking phenomenon is a critical issue in the production of calcium carbonate–cholecalciferol (vitamin D3) chewable tablets, primarily driven by the hygroscopicity and reactivity of citric acid, which is used as a flavor-masking agent. This study aims to evaluate and determine the optimal method for mitigating sticking by modifying citric acid excipients using two approaches: granulation with mannitol (F1: 0.5%, F2: 1%) and coating with HPMC (F3: 0.5%, F4: 1%). The evaluation was conducted on the properties of the granule mass and quantitatively measured the percentage of sticking in industrial-scale modifications for 24 hours. The results showed that the control formula (F0), without modification, had the lowest sticking percentage (10.88%) and the highest moisture content (3.36%), as indicated by a "passable" flow property with a compressibility index of 21.47%. The 1% HPMC coating modification method (F4) was successful in eliminating stickiness to 0%, supported by moisture-control data (2.25%) and a significant improvement in powder-flow properties to “fair,” with a compressibility index of 17.06%. Although the 1% mannitol granulation method (F2) is relatively effective in reducing stickiness (0.85%), the 1% HPMC coating (F4) is more effective at physically isolating citric acid. This study concludes that the HPMC coating method is superior to the granulation method for physically isolating citric acid, yielding stable, non-sticking calcium carbonate–cholecalciferol chewable tablets.